Knowledge Management Mediator Strategy for Resolving Industrial Conflicts in Makassar - Seri Suriani; Kafrawi Yunus; Thamrin Abduh (Journal of Public Administration and Government, 2023)
Conflicts within a company that are handled quickly and precisely will result in new ideas, changes, and better working relationships. This research was conducted to analyze how conflicts that occur in companies can be mediated using the knowledge management approach. The analysis technique used in this study is qualitative, using the interview method addressed to dispute mediators at the Makassar City Manpower Office and the Chairperson of the Labor Union. The results of the study show that good knowledge management, owned by mediators, is able to handle conflicts more quickly and precisely. Furthermore, tacit knowledge is knowledge in the form of experience and expertise possessed by each mediator that is most needed to unravel corporate conflicts in Makassar